Предмет: Алгебра,
автор: Аноним
решите уравнение
(х+3)(2-х)=0
Ответы
Автор ответа:
0
(х+3)(2-х)=0
х+3=0 или 2-х=0
х=-3 х=2
Ответ: -3 и 2
х+3=0 или 2-х=0
х=-3 х=2
Ответ: -3 и 2
Автор ответа:
0
(х+3)*(2-х)=0
2х+6-3х-х²=0
-х²-х+6=0
Д=1-4*(-1)*6=1+24=25=5²
х1=1-5-2=-4-2=2
х2=1+5-2=6-2=-3
2х+6-3х-х²=0
-х²-х+6=0
Д=1-4*(-1)*6=1+24=25=5²
х1=1-5-2=-4-2=2
х2=1+5-2=6-2=-3
Похожие вопросы
Предмет: Геометрия,
автор: ganstermmm666
Предмет: Русский язык,
автор: kristiusha92
Предмет: Русский язык,
автор: adelinakrg09
Предмет: Литература,
автор: Аноним